Thyroid Diseases in Childhood Recent Advances from Basic Science to Clinical Practice - Bona, Gianni.; Bona, Gianni.; De Luca, Filippo.; De Luca, Filippo.; Monzani, Alice.; Monzani, Alice. (Springer International Publishing : Imprint: Springer, 2015)
This book covers the entire spectrum of thyroid diseases in childhood, focusing on the recent advances that have been achieved, from progress in basic science research through to novel or improved approaches to diagnosis and treatment. Introductory chapters discuss thyroid embryogenesis and the role of thyroid hormones in fetal development. The two contrasting forms of thyroid dysfunction, hypo- and hyperthyroidism, are then considered in depth, with particular attention to the molecular causes of congenital hypothyroidism. Among the other topics addressed are autoimmune thyroiditis, thyroid nodules, and pediatric neoplasms. The book concludes with an overview of promising therapeutic approaches, such as stem cell therapy. Each topic is treated by an eminent expert in the field, ensuring consistently high quality. Thyroid Diseases in Childhood will be an important source of information for endocrinologists, pediatricians, oncologists, and gynecologists, as well as other professionals interested in this topic.